Regulatory Reform, Competition, and Innovation : A Case Study of the Mexican Road Freight Industry - Dutz, Mark A.; Hayri, Aydin; Ibarra, Pablo (World Bank, Washington, DC, 2015)
Discussions of competition and regulatory reform typically focus on price and quantity effects. But improving certain infrastructure services can also stimulate entry, and competition in user industries downstream, allowing new firms to enter, incumbent users to offer new products, and rivalry to intensify. The authors present a case study of how innovations in road freight services affect selected downstream users of those services after regulatory reform. After a period of rigid regulation, and heavy government interference, Mexico in 1989 developed a new policy framework for road transport, with free entry, and market-based price setting. The result: faster, more reliable trucking has allowed user companies to offer new, previously unavailable products, and to reach new areas with existing products. Cheaper, more customer-responsive trucking services have allowed logistical innovations in user firms, and some user firms have decided not to keep their own fleets of trucks, but to outsource trucking services on the open market, thereby converting fixed costs to variable costs. For one fertilizer company, the benefits of reform included a ten percent improvement in operating margin. Successful reform requires careful planning and execution, and political support at high levels. Regulatory reform also profoundly changes the sectoral institution formerly responsible for the regulation. Enough resources should be provided to help organizations in the reformed industry make the transition to the post-reform environment - helping with such tasks as defining the organizations new role, and facilitating the redeployment of staff. The national competition agency can help greatly in laying the groundwork for reform by making a compelling case for the reforms expected benefits. After reform, the competition agency should also help with enforcement, to ensure that the cozy, cartel-like behavior stimulated by tight entry restrictions does not persist. In Mexico, three strong interventions were required to discipline attempted anti-competitive practices in the trucking industry in the years following reform.